The Impact of Female Leadership in Collegial Courts on Time to Render Merits Decisions: Evidence from the Norwegian Supreme Court. (1st November 2022) - Nie, Mintao; Grendstad, Gunnar; Shaffer, William R.; Waltenburg, Eric N.
Abstract: What is the effect of gender on the deliberative process of judging? Drawing on previous research on female leaders' inclination to foster a more inclusive and collaborative decision-making process, we argue that decision making takes more time in a collegial court when female justices preside over decisional panels. Analyzing an original data set on cases decided by the Norwegian Supreme Court between 2008 and 2019, we find that when a woman is the presiding justice, the duration of case disposition time increases. This effect, however, persists for only eight days. Our finding suggests that institutional practices take effect over gendered effects.